Estudo do potencial efeito neuroprotetor do canabidiol e seus análogos, bem como do N,N-dimetiltriptamina e da harmina, componentes da ayahuasca, frente à neurotoxicidade induzida pelo etanol - Almeida, Carolina Aparecida De Faria (2024)
The treatment of alcohol use disorder (AUD) is a clinical challenge due to the high incidence of relapse. Several substances, such as psychedelics, have been studied in this context. The aim of this study was to investigate the therapeutic potential of cannabidiol and its analogues (PQM-242 and PQM-249), DMT and HRM, in preclinical models related to AUD. In vivo studies were carried out in Swiss mice to evaluate the anxiolytic and antidepressant effects of cannabidiol and its analogues through the elevated plus maze and forced swimming tests. The effects of DMT and HRM, components of ayahuasca, on behavioral sensitization to ethanol were also evaluated. In vitro studies were conducted to assess the effects of cannabidiol and its analogues, DMT, and HRM against ethanol-induced neurotoxicity in SH-SY5Y cells. The highest non-toxic effect concentration (NOAEL) was determined for all compounds. The tetrazolium bromide (MTT) assay was used to determine cell viability, and celular stages of death and mollecular changes were evaluated using annexin/PI and Western blot tests for Bax and Bcl-2, respectivaly. In in vivo assays, cannabidiol (10 mg/kg) and its analogues PQM-242 (3 mg/kg) and PQM-249 (1 mg/kg) had anxiolytic and antidepressant effects. On behavioral sensitization protocol, only HRM was able to to attenuate the expression of sensitization. In in vitro assays, ethanol-induced neurotoxicity caused apoptosis and late apoptosis in SHSY5Y cells, and also increased Bax levels. All compounds - CBD and its analogues PQM-242 and PQM-249, DMT, HRM at a concentration of 10 µM, and a 1:2 DMT/HRM association - showed a neuroprotective effect, protecting SH-SY5Y cells from apoptosis and late apoptosis induced by ethanol. However, only the PQM-242 analogue was able to block the increase in Bax levels induced by ethanol.